In Silico Approach of DNA Barcoding in Cattleya Orchid using nrDNA and matK Markers - Wiharyanti, Risma; Mercuriani, Ixora Sartika; Yulianti, Evy; Kuswandi, Paramita Cahyaningrum (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2025)
The Cattleya genus is one of the most commercially valuable orchids. Identifying these orchids based on morphological and phenotypic traits has been challenging. Accurate identification is crucial for distinguishing between native and hybrid species and determining the protected status of certain Cattleya orchids. This research explored potential markers using nrDNA and matK locus for DNA barcoding of the Cattleya genus through an in silico approach. All sequences were collected from the NCBI and analyzed using ClustalX2 for alignment, BioEdit for conversion, and MEGA11 for phylogenetic tree construction. The results revealed that nrDNA showed higher genetic variation compared to matK. However, neither phylogenetic tree could discriminate species precisely, as some Cattleya species were positioned closer to the outgroup. These findings can be used as a reference to support identification of Cattleya using molecular marker. Keywords: Cattleya, matK, molecular barcode, nrDNA